1995
DOI: 10.1111/j.1432-1033.1995.027_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Directed Mutagenesis and Sugar‐Binding Properties of the Wheat Germ Agglutinin Mutants Tyr73Phe and Phe116Tyr

Abstract: Wheat germ agglutinin is a dimeric lectin composed of two identical subunits. Each subunit consists of four homologous hevein-like domains of 42 or 43 amino acids each. Amino acid residues at the same position in each domain involved in sugar binding are thought to play a similar role in sugar binding. In order to clarify the role of the amino acid residue at domain position 30 of wheat germ agglutinin isolectin 2 (WGA2) in sugar binding, two WGA2 variants each containing a mutation, either Tyr73-Phe (domain B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
1
12
1
Order By: Relevance
“…Under such conditions, a complex equilibrium is taking place between ligand binding and lectin dimerization. Other binding studies on WGA (16,(42)(43)(44)(45)(46)(47)(48) used lectin concentrations similar to or even smaller than those used by Bains et al It follows then that a reexamination of the sugar-binding properties of WGA is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Under such conditions, a complex equilibrium is taking place between ligand binding and lectin dimerization. Other binding studies on WGA (16,(42)(43)(44)(45)(46)(47)(48) used lectin concentrations similar to or even smaller than those used by Bains et al It follows then that a reexamination of the sugar-binding properties of WGA is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between the binding sites lie in three tyrosine residues and a serine from one subunit while variability between the binding sites is seen in interaction involving residues from the other subunit (Wright, 1990;Nagahora et al, 1995). A different binding site was observed in the crystal structure o f the galactose specific lectin Jacalin complexed with M eaGal (Sankaranarayanan et al, 1996).…”
Section: Asn 14 Asn133mentioning
confidence: 98%
“…Mechanisms for carbohydrate recognition have been studied in several lectins (1). Recently, x-ray crystallographic studies and mutational studies have demonstrated that several amino acid residues play key roles in lectin-carbohydrate interaction (2,3). Physarum polycephalum produces two types of lectins, termed haemagglutinins I and II, which have different molecular masses and carbohydrate specificities, but have relatively high afffmity for thyroglobulin (4).…”
Section: Introductionmentioning
confidence: 99%